Birth Defects Data From Population-Based Birth Defects Surveillance System in a District of Southern Jiangsu, China, 2014–2018 - Zhou, Ying; Mao, Xueqin; Zhou, Hua; Wang, Li; Qin, Zhiqiang; Cai, Zhengmao; Yu, Bin (Frontiers in Public Health, 2020)
As a population-based national surveillance region, Tianning District confronts with great challenges in birth defects (BDs) prevention. We aimed to describe the epidemiology of BDs in infants (including dead fetus, stillbirth, or live birth between 28 weeks of gestation and 42 days after birth) in Tianning District from 2014 to 2018. The data was collected from the national birth defect surveillance system. The prevalence rates of BDs were calculated by poisson distribution. Trends of incidence and the associations of regarding perinatal characteristics with BDs were analyzed by poisson regression. During the study period, the prevalence of BD was 155.49 per 10,000 infants. The ten leading BDs were congenital heart defects (CHD), polydactyly, Congenital malformation of kidney (CMK), syndactyly, cleft palate, hypospadias, Congenital hypothyroidism (CH), congenital atresia of rectum and anus, congenital talipes equinovarus (CTE), and microtia. A significant increase in the prevalence of CHD was observed with a prevalence rate ratio (PRR) of 1.191. Gravidity ≥ 3 (PRR = 1.38) and multiple births (PRR = 2.88) were risk factors for BDs. Premature delivery (PRR = 4.29), fetal death or stillbirth (PRR = 24.79), and infant death (PRR = 43.19) were adverse consequences of BDs. Strengthening publicity and education, improving the ability of diagnosis and monitoring, expanding surveillance time quantum of BDs system may be warranted.